Perancangan dan Implementasi Aplikasi Keuangan Gereja Jemaat UNAI Berbasis Web Menggunakan Yii Framework - Andrew Fernando Pakpahan; Valentine Siagian; James Sylvanus Ulyreke (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2019)
UNAI church has many members and large amount of financial activities. Before this research is done the financial transactions were recorded with different applications between income and expense. Thus requiring a long process to crate the final financial statement. In this research, a financial application that combines the income and expense recording in an easy-to-use application is designed and implemented. This application is designed with prototyping method, where an application prototype can be implemented and revised as user’s demands . This financial application provides membership recording, departement management, budget year management, budgeting, income recording, expense recording, cash advance management and provides several reporting such as: membership report, departement report, daily income report, monthly income report, expense report, budget report and income and expense combined report. Keywords: Financial application, Church Financial Application, Web Application, Yii Framework